Med domom in svetom - Nagode, Aleš (Muzikološki zbornik, 2012)
The article presents a new view on the material linked to Risto Savin's songs for voice and piano. It draws attention to several songs that have thus far been unaccounted for and uses a range of facts to correct the established chronology of Savin's songs. The results of this research considerably alter our understanding of Savin's creativity. His decision to associate himself with the Slovene national movement was not an instant turning point, as has been believed, but rather a result of a long-term response to the intiatives from the cultural environment in which he worked.
Keywords: 19./20.st.; narodni preporod; samospevi; Savin, Risto; vokalna glasba